Estudio de factibilidad para la creación de un centro nutricionista para personas diabéticas en el Cantón Quevedo. año 2013. - Proaño Erazo, Elsa Carolina (2013)
This research was conducted in order to determine the feasibility of creating a Nutritionist Diabetic Center in Canton Quevedo. The project is aimed at the diabetic population both men and women. Through the market survey it was found that there is no direct competition, and according to question 10 of the study of 303 people with diabetes in the city, 302 indicated that if they agree with the establishment of the center, as well as 77% stated that they agree that the nutritionist center provides the following services: diabetes education, dietary menu and natural products as to question 11. The investment required for the Centre Nutritionist "NUTRIDIA" is $ 45,758.39 being 60% funding provided by three partners and 40% financed by a loan from the National Development Bank with an interest rate of 15% at 5 year term. The economic and financial study determines that the project is viable and profitable, this based on financial indicators, which resulted in an NPV of $ 110,272.23 IRR of 92%, an R B / C of $ 2.41 and a recovery period of 1 year and 4 months.